Transitional Markers in The Argumentative Compositions of The English Department Students - Linda Agustin; Agustinus Ngadiman (Widya Mandala Surabaya Catholic University, 2013)
Coherence in a composition is achieved when there is a clear transition or link between its major parts. This study is conducted to reveal the kinds and uses of transitional markers signaling reason and conclusion in argumentative compositions. The data source was 16 argumentative compositions of Writing 3 students of an English Department Surabaya. The study reveals that there were 31 (156 frequency of occurrences) transitional markers signaling reason and conclusion found, which consists of 21 (110 frequency of occurrences) markers functioning as reason, and 10 (46 frequency of occurrences) others functioning as conclusion. The forms of transitional markers signaling reason were: word and phrase form. The writer found 7 (83 frequency of occurrences) word and 14 (27 frequency of occurrences) phrase forms of reason transitional markers. She also found 4 (34 frequency of occurrences) word form, 3 (9 frequency of occurrences) phrase form, and 3 (3 frequency of occurrences) clause form of transitional markers signaling conclusion. Among all of those transitional markers, there were 93 times of appropriate and 17 times of inappropriately used transitional markers signaling reason; and 37 times of appropriate and 9 times of inappropriately used transitional markers signaling conclusion. Based on the findings of the analysis above, it can be concluded that the inappropriateness used of the transitional markers found mostly happen in the presence of comma and because of the influence of Bahasa Indonesia.